Compulsory Education and Jack-of-all-trades Entrepreneurs - Robin Douhan (Research Institute of Industrial Economics (IFN), 2009)
Can educational institutions explain occupational choice between wage employment and entrepreneurship? This paper follows Lazear's (2005) Jack-of-all-trades hypothesis according to which an individual with a more balanced set of abilities is more likely to enter into entrepreneurship. In the theoretical model proposed, abilities are an outcome of talent and educational institutions. Institutions, in turn, differ with respect to mandatory time in school and the scope of the curriculum. Implications of the theory are tested using Swedish data for a school reform. Empirical results support the main theoretical predictions.
Keywords: I21; J24; L26; 330; Human Capital; Occupational Choice; Entrepreneurship; Education Institutions; Humankapital; Berufswahl; Entrepreneurship-Ansatz; Bildungseinrichtung; Theorie